Aperiodic Subshifts of Finite Type on Groups Which Are Not Finitely Generated - Barbieri-Lemp, S (American Mathematical Society, 2023)
We provide an example of a non-finitely generated group which admits a nonempty strongly aperiodic subshift of finite type. Furthermore, we completely characterize the groups with this property in terms of their finitely generated subgroups and the roots of their conjugacy classes. © 2023 American Mathematical Society.